AMP-activated protein kinase mediates (-)-epigallocatechin-3-gallate (EGCG) to promote lipid synthesis in mastitis cows - Chunli Hu; Wenli Dou; Xuehu Ma; Yanhao An; Dezhi Wang; Yanfen Ma (Animal Biotechnology)
Mastitis, a serious threat to the health and milk production function of dairy cows decreases milk quality. Blood from three healthy cows and three mastitis cows were collected in this study and their transcriptome was sequenced using the Illumina HiSeq platform. Differentially expressed genes (DEGs) were screened according to the |log2FoldChange| > 1 and P-value < 0.05 criteria. Pathway enrichment and functional annotation were performed through KEGG and GO analyses. Finally, the mechanism of the AMP-activated protein kinase (AMPK) mediation of (-)-epigallocatechin-3-gallate (EGCG) to promote lipid metabolism in mastitis cows was analyzed in bovine mammary epithelial cells (BMECs). Transcriptome analysis revealed a total of 825 DEGs, with 474 genes showing increased expression and 351 genes showing decreased expression. The KEGG analysis of DEGs revealed that they were mainly linked to tumour necrosis factor, nuclear factor-κB signalling pathway, and lipid metabolism-related signalling pathway, whereas GO functional annotation found that DEGs were enriched in threonine and methionine kinase activity, cellular metabolic processes, and cytoplasm. AMPK expression, which is involved in several lipid metabolism pathways, was downregulated in mastitis cows. The results of in vitro experiments showed that the inhibition of AMPK promoted the expression of lipid synthesis genes in lipopolysaccharide-induced BMECs and that EGCG could promote lipid synthesis by decreasing the expression of AMPK and downregulating the expression of inflammatory factors in inflammatory BMECs. In conclusion, our study demonstrated that AMPK mediated EGCG to inhabit of inflammatory responses and promote of lipid synthesis in inflammatory BMECs.